'Gain with no pain': Anabolic-androgenic steroids trafficking in the UK. (November 2016) - Antonopoulos, Georgios A.; Hall, Alexandra
Anabolic-androgenic steroids are performance and image enhancing drugs (PIED) that can improve endurance and athletic performance, reduce body fat and stimulate muscle growth. The use of steroids has been studied extensively in the medical and psychological literature, as well as in the sociology of sport, health and masculinity. From the late 2000s, the worldwide trade in steroids increased significantly. However, trafficking in steroids remains a largely under-researched criminological phenomenon with a few notable exceptions. Currently in the UK there are only small and fragmented pieces of information available relating to steroids trafficking in autobiographical accounts of professional criminals. Drawing on original empirical data, the purpose of this article is to provide an account of the social organization of the steroids trafficking business in the UK. The trade in steroids is decentralized, highly flexible with no hierarchies, and open to anyone willing to either order the merchandise online or travel to producing countries and obtain steroids in bulk from legitimate manufacturers. The patterns of trafficking of this specific type of substance are patently conditioned by its embeddedness in the gym/bodybuilding scene and this greatly affects relations between actors in the business. In the steroids market, one typically encounters a multitude of individuals likely to drift between legality and illegality, online and offline, use and supply.